Design Rules for Self‐Assembly of 2D Nanocrystal/Metal–Organic Framework Superstructures. Issue 40 (11th September 2018) - Qiu, Fen; Edison, John R.; Preisler, Zdenek; Zhang, Yan‐Fang; Li, Guo; Pan, Aizhao; Hsu, Chih‐Hao; Mattox, Tracy M.; Ercius, Peter; Song, Chengyu; Bustillo, Karen; Brady, Michael A.; et al.
Abstract: We demonstrate the guiding principles behind simple two dimensional self‐assembly of MOF nanoparticles (NPs) and oleic acid capped iron oxide (Fe3 O4 ) NCs into a uniform two‐dimensional bi‐layered superstructure. This self‐assembly process can be controlled by the energy of ligand–ligand interactions between surface ligands on Fe3 O4 NCs and Zr6 O4 (OH)4 (fumarate)6 MOF NPs. Scanning transmission electron microscopy (TEM)/energy‐dispersive X‐ray spectroscopy and TEM tomography confirm the hierarchical co‐assembly of Fe3 O4 NCs with MOF NPs as ligand energies are manipulated to promote facile diffusion of the smaller NCs. First‐principles calculations and event‐driven molecular dynamics simulations indicate that the observed patterns are dictated by combination of ligand–surface and ligand–ligand interactions. This study opens a new avenue for design and self‐assembly of MOFs and NCs into high surface area assemblies, mimicking the structure of supported catalyst architectures, and provides a thorough fundamental understanding of the self‐assembly process, which could be a guide for designing functional materials with desired structure. Abstract : The guiding principles behind simple 2D self‐assembly of MOF nanoparticles (NPs) and oleic acid capped iron oxide (Fe3 O4 ) NCs into a uniform two‐dimensional bi‐layered superstructure are described. The self‐assembly process can be controlled by the energy of ligand–ligand interactions between surface ligands on Fe3 O4 NCs and Zr6 O4 (OH)4 (fumarate)6 MOF NPs.